CURRENT CHALLENGES OF THE RESTAURANT BUSINESS IN UKRAINE TAKING INTO ACCOUNT THE CONDITIONS OF WAR AND REQUIREMENT OF SOCIETY (Development Service Industry Management, 2024)
The article highlights the challenges faced by the restaurant business of Ukraine in connection with the beginning of the war. The identified problems caused significant damage, which led to the closure of more than 25% of public catering establishments. The frontline regions were the most affected: Luhansk, Donetsk, Zaporizhzhya, Kharkiv, Kherson, Dnipropetrovsk, Sumy. The initial blows to business were a significant outflow of qualified personnel, disruption of industrial and economic relations and deterioration of the economic well-being of the population, which led to a significant reduction in demand. But it is not only the war that damages the restaurant business. The challenges faced by restaurateurs are caused by the change in society itself as a result of scientific and technological progress that changes the global processes of the external environment. The needs of consumers today are radically different from those that were in demand 5-10 years ago. The restaurant business is also forced to adapt to the trends set by the modern rhythm of life, which is the need to use automation and digitalization, the presence of business in social networks and control of customer feedback, greening and menu labeling. A large number of restaurants in the USA and Europe offer their customers food labeling. Specifying the amount of proteins, carbohydrates, and fats in dishes is becoming commonplace. Today, in the countries of the European Union, it is mandatory to indicate whether the products are made entirely of environmentally friendly products, the country (region) of their origin, what ingredients the dish is made of, whether it includes genetically modified products, products of biological life (insects, worms, etc. .) in order to increase consumer value. The restaurant business is going through some of the most difficult times, because the competitive pressure is growing from hypermarkets of various types, which offer to visit them more and more often for lunch or coffee while simultaneously making purchases of both building materials and home decor. Also, the generation of millennials is coming to the forefront, which is highly solvent and has unique tastes and preferences. At the same time, the spread of global cuisine is taking place, which will only determine the direction and pace of development of the restaurant business. Highlighting the above-mentioned trends will make it possible to minimize the impact of the war on the domestic restaurant business and allow it to adapt to the challenges of the future.
Keywords: war; restaurant business; challenges; scientific and technological progress; society; millennials